Oral antidiabetic medication adherence and glycaemic control among patients with type 2 diabetes mellitus: a cross-sectional retrospective study in a tertiary hospital in Saudi Arabia - Bander Balkhi; Monira Alwhaibi; Nasser Alqahtani; Tariq Alhawassi; Mansour Mahmoud; Mansour Almetwazi; Sondus Ata; Khalid M Kamal (BMJ Open)
Objectives The purpose of this study is to measure the adherence rates of oral antidiabetic drugs (OADs) in patients with type 2 diabetes mellitus (T2DM) and assess the relationship of glycaemic control and adherence to OADs after controlling for other associated factors.Design Cross-sectional retrospective study.Setting Large tertiary hospital in the central region of Saudi Arabia.Participants 5457patients aged 18 years and older diagnosed with T2DM during the period from 1 January 2016 to 31 December 2016.Primary and secondary outcome measures The modified medication possession ratio (mMPR) was calculated as a proxy measure for adherence of OADs. The factors associated with OADs non-adherence and medication oversupply were assessed using multinomial logistic regression models. The secondary outcomes were to measure the association between OADs adherence and glycaemic control.Results Majority of patients with T2DM were females (n=3400, 62.3%). The average glycated haemoglobin was 8.2±1.67. Among the study population, 48.6% had good adherence (mMPR >0.8) and 8.6% had a medication oversupply (mMPR >1.2). Good adherence was highest among those using repaglinide (71.0%) followed by pioglitazone (65.0%) and sitagliptin (59.0%). In the multivariate analysis, women with T2DM were more likely to have poor adherence (adjusted OR (AOR)=0.76, 95% CI=0.67, 0.86) compared with men. Also, medication oversupply was more likely among patients with hyperpolypharmacy (AOR=1.88, 95% CI=1.36, 2.63), comorbid osteoarthritis (AOR=1.72, 95% CI=1.20, 02.45) and non-Saudi patients (AOR=1.53, 95% CI=1.16, 2.01). However, no association was found between glycaemic control and adherence to OADs.Conclusion The study findings support the growing concern of non-adherence to OADs among patients with T2DM in Saudi Arabia. Decision makers have to invest in behavioural interventions that will boost medication adherence rates. This is particularly important in patients with polypharmacy and high burden of comorbid conditions.